Environmental drivers and genomic architecture of trait differentiation in fire-adapted Banksia attenuata ecotypes - He, Tianhua; Lamont, Byron; Enright, N.; D'Agui, Haylee; Stock, W. (2018)
© 2018 Institute of Botany, Chinese Academy of Sciences Trait divergence between populations is considered an adaptive response to different environments, but to what extent this response is accompanied by genetic differentiation is less clear since it may be phenotypic plasticity. In this study, we analyzed phenotypic variation between two Banksia attenuata growth forms, lignotuberous (shrub) and epicormic resprouting (tree), in fire-prone environments to identify the environmental factors that have driven this phenotypic divergence. We linked genotype with phenotype and traced candidate genes using differential gene expression analysis. Fire intervals determined the phenotypic divergence between growth forms in B. attenuata. A genome-wide association study identified 69 single nucleotide polymorphisms, putatively associated with growth form, whereas no growth form- or phenotype-specific genotypes were identified. Genomic differentiation between the two growth forms was low (Fst = 0.024). Differential gene expression analysis identified 37 genes/transcripts that were differentially expressed in the two growth forms. A small heat-shock protein gene, associated with lignotuber presence, was differentially expressed in the two forms. We conclude that different fire regimes induce phenotypic polymorphism in B. attenuata, whereas phenotypic trait divergence involves the differential expression of a small fraction of genes that interact strongly with the disturbance regime. Thus, phenotypic plasticity among resprouters is the general strategy for surviving varying fire regimes.